2016
DOI: 10.1088/0953-4075/49/11/115203
|View full text |Cite
|
Sign up to set email alerts
|

Solution of the proton-hydrogen scattering problem using a quantum-mechanical two-center convergent close-coupling method

Abstract: Details of the recently developed quantum-mechanical two-center convergent close-coupling approach (Abdurakhmanov et al 2016 J. Phys. B: At. Mol. Phys. 49 03LT01) to proton-hydrogen scattering are presented. The formulation is based on the exact (fully quantum-mechanical) three-body Schrödinger equation. The total scattering wavefunction is expanded using a two-center pseudostate basis. This allows one to include all underlying processes, namely, direct scattering and ionization, electron capture into bound an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 77 publications
3
42
0
Order By: Relevance
“…Theoretical results from the aforementioned studies [2,4,8,9] are shown alongside the present results. For H(1s) collisions the included results from [17] are from calculations based on the quantum-mechanical convergent close-coupling (QM-CCC) method, which is viewed as an exact treatment of the quantum-mechanical threebody Schrödinger equation. It is noteworthy that the AOCC-GTO calculation in [10] considered all 2p m initial states, but the reported cross sections are averaged over the m substates, and thus, not appropriate to compare with the results shown in the present figure. Comparisons of the present TC-BGM capture cross sections for H(2p) collisions, when averaged across the m states, agree with the AOCC-GTO calculation within 2% or better.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical results from the aforementioned studies [2,4,8,9] are shown alongside the present results. For H(1s) collisions the included results from [17] are from calculations based on the quantum-mechanical convergent close-coupling (QM-CCC) method, which is viewed as an exact treatment of the quantum-mechanical threebody Schrödinger equation. It is noteworthy that the AOCC-GTO calculation in [10] considered all 2p m initial states, but the reported cross sections are averaged over the m substates, and thus, not appropriate to compare with the results shown in the present figure. Comparisons of the present TC-BGM capture cross sections for H(2p) collisions, when averaged across the m states, agree with the AOCC-GTO calculation within 2% or better.…”
Section: Resultsmentioning
confidence: 99%
“…Experiment: Shah1981 [18]; Shah1987 [19]; and Shah1998 [20]. Theory: QM-CCC [17]; WP-CCC [9]; AOCC-GTO [10]; and present TC-BGM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A proper formulation of Ps-formation processes requires a combined basis consisting of two independent basis sets for each of the centres which makes theoretical studies considerably more challenging than for electronscattering. Furthermore, the positron-atom system is an ideal prototype of the ubiquitous collision systems such as proton-atom scattering, where charge-exchange processes also require a two-centre treatment, see Abdurakhmanov et al [41] for example.…”
Section: A Positron Scatteringmentioning
confidence: 99%